Information Systems for Crisis Management – Current Applications and Future Directions - Jozef Ristvej; Adam Zagorecki (Communications - Scientific letters of the University of Zilina, 2011)
The management of crisis situations is undergoing rapid changes due to advances of Information Technology. We discuss the role of information systems in supporting decision making processes in crisis management. The crisis management poses particular challenges for information systems – it is characterized by dynamic, complex environments involving many actors in often very unique and extreme situations. We review the roles, benefits and challenges of information systems’ application to different phases of the crisis management. We argue that for the different phases of the crisis management, the different types of information systems varying in the aspects such as use scenarios, user requirements, critical technologies, etc. are suitable. Finally, we outline the directions for future research and applications for the field of the support systems for the emergency management.